(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The word personality means the character, temper, temperament, the disposition, or we can say dominant quality which distinguishes someone. As per any visionary’s aspect the tolerance of stress, consciousness, agreeableness, openness, and the extroversion might be the components of a personality" In the modern education it is very essential to work on the personality development of students. The wholesome personality development builds the confidence and self-esteem of students. It develops-leadership skills, problem solving skills, communication skills, resilience and adaptability, emotional intelligence, and the positive outlook on life. The fields of science and sports also play an important role in the wholesome personality development of learners.